ANALISIS KINERJA KEUANGAN PEMERINTAH KOTA LHOKSEUMAWE - Wahyuddin, Wahyuddin; Sugianal, Nora (Department of Accounting, Faculty of Economics & Business, 2017)
This study aims to analyze the financial performance of Lhokseumawe City Â using the Fiscal Decentralization Degree Ratio, Independence Ratio, PAD Effectiveness Ratio, Regional Financial Efficiency Ratio, and Harmony Ratio. The data used in this study are quantitative data, namely, Budget Realization Reports sourced from BPKD (Regional Financial Management Agency of Lhokseumawe City. Data collection uses documentation method. Data analysis method used is quantitative descriptive with the formula of Fiscal Decentralization Ratio, Independence Ratio, Ratio Effectiveness of PAD, Regional Financial Efficiency Ratio and Harmony Ratio The results of this study indicate that the financial performance of the government of Lhokseumawe City uses a Degree of Decentralization Ratio which can be categorized as very poor, because the average is 6.03%, the Regional Financial Independence Ratio is still classified instructive relationship because the average magnitude of this ratio is 7.82%, PAD Effectiveness Ratio of the financial performance of Lhokseumawe CityÂ is less effective because the average effectiveness is below 100% which is 90.55%, Regional Financial Efficiency Ratio can be said to be less efficient because the average of regional financial efficiency of Lhokseumawe City is 96.59%, the Harmony Ratio is known that the average regional operating expenditure is still very high at 57.84% compared to the average capital expenditure of 23.29%. So, it can be said that the Regional Government is still not good at managing the government.